Characteristics and risk factors of Plasmodium falciparum malaria in Eastern and Central Nepal - Banjara, MR; Sirawaraporn, W; Petmitr, S; Imwong, M; Joshi, AB; Chavalitshewinkoon-Petmitr, P (Kathmandu University Medical Journal, 2010)
Background: Very limited information is available on epidemiology of falciparum malaria in Nepal. Such information is very important for malaria control programmes. It is believed that malaria in Eastern region is imported from border districts of India and local transmission follows whereas it is indigenous in Central region. Therefore, the characteristics and risk factors of malaria are believed to be different in Eastern and Central Nepal. Objective: The objective of the study is to describe and compare the characteristics and risk factors of falciparum malaria in Eastern and Central Nepal. Materials and methods: This cross-sectional study was conducted in falciparum malaria endemic districts of Eastern and Central Nepal, during the period 2007 to 2008. We identified and collected information from 106 patients (62 from Eastern and 44 from Central region). Patient examination, clinical and laboratory assessment were done and patients were interviewed using structured questionnaire for malaria related characteristics, risk factors and behaviours. Results: There were significant differences in risk factors and characteristics of falciparum malaria in the Central than the Eastern region. In the Central region, male, illiteracy and thatched roof hut were significant risk factors of falciparum malaria patients as compared to the Eastern region. Visits outside within one months, previous malaria within three months, taking antimalarial before confirmatory diagnosis were significantly higher in patients of the Eastern region as compared to the Central region. Conclusion: Falciparum malaria in Nepal should not be seen as similar entity, and different strategies for prevention and control is needed for its diverse characteristics and endemicity. Key words: Eastern and Central Nepal; falciparum malaria; risk factors DOI: 10.3126/kumj.v7i4.2758 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 378-382